2017
DOI: 10.1371/journal.pone.0183996
|View full text |Cite
|
Sign up to set email alerts
|

Crumble analysis of the historic sympatric distribution between Dendrortyx macroura and D. barbatus (Aves: Galliformes)

Abstract: In Mexico, the Long-tailed Wood-Partridge (Dendrortyx macroura) is distributed in the mountains of the Trans-Mexican Volcanic Belt, Sierra Madre del Sur and Sierra Norte de Oaxaca; while the Bearded Wood-Partridge (D. barbatus) is distributed in the Sierra Madre Oriental (SMO). There is a controversial overlap in distribution (sympatry) between these two species (on the Cofre de Perote and Pico de Orizaba volcanoes, SMO and Sierra Norte de Oaxaca), based on the ambiguity and current lack of information regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our analyses indicated that the origin and diversification of the A. taeniata–graminea species complex has been most likely shaped by the complex geologic history of the region and distributional changes of the pine–oak forests that they inhabit. Other groups of organisms inhabiting these cloud forests share similar cladogenesis patterns, including rodents (Ávila‐Valle et al, 2012; Hardy et al, 2013; León‐Paniagua et al, 2007), amphibians (Caviedes‐Solis & Leaché, 2018; García‐Castillo et al, 2018; Parra‐Olea et al, 2020), lizards (Bryson et al, 2012) and birds (Mota‐Vargas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses indicated that the origin and diversification of the A. taeniata–graminea species complex has been most likely shaped by the complex geologic history of the region and distributional changes of the pine–oak forests that they inhabit. Other groups of organisms inhabiting these cloud forests share similar cladogenesis patterns, including rodents (Ávila‐Valle et al, 2012; Hardy et al, 2013; León‐Paniagua et al, 2007), amphibians (Caviedes‐Solis & Leaché, 2018; García‐Castillo et al, 2018; Parra‐Olea et al, 2020), lizards (Bryson et al, 2012) and birds (Mota‐Vargas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…3.92 Ma (León‐Paniagua et al, 2007). Previous biogeographical studies have documented that the Papaloapan basin has played an important role promoting allopatric speciation in highland organisms with low vagility, such as small mammals (Carleton et al, 2002; Guevara & Sánchez‐Cordero, 2018; Rogers et al, 2007; Sullivan et al, 1997; Vallejo & González‐Cózatl, 2012), lizards ( A. antauges and A. juarezi ; Solano‐Zavaleta et al, 2017; Xenosaurus grandis and X. manipulus ; Nieto‐Montes de Oca et al, 2022), pine–oak forest birds (Mota‐Vargas et al, 2017) and troglobiotic scorpions (Santibáñez‐López et al, 2014). In the same line, our results suggest that climatically unfavourable areas across these low‐elevation areas during both the LGM and present (Figure 5) limited and continue to limit secondary contact between populations at both sides of the valley of the Santo Domingo River (Sierra Mazateca and Sierra de Juárez).…”
Section: Discussionmentioning
confidence: 99%